One-Dimensional Metals : Conjugated Polymers, Organic Crystals, Carbon Nanotubes and Graphene /: Conjugated Polymers, Organic Crystals, Carbon Nanotubes and Graphene. ([2015]) - Roth, S (Siegmar), 1940-; Carroll, David L (David Loren)
No abstract available